Factors associated with child passenger motorcycle helmet use in Cambodia. Issue 2 (3rd April 2018) - Merali, Hasan S.; Bachani, Abdulgafoor M.
ABSTRACT: This study examines factors associated with child passenger helmet use in five Cambodian provinces. We performed an analysis of periodic roadside observations of helmet use over a four-year period. A total of 62, 039 child passengers 12 years of age and younger met inclusion criteria and were included in the analysis. Overall, 1369 (2.1%) of child passengers were observed to be wearing a helmet. Most significantly, children were six times more likely to wear a helmet if the driver was wearing a helmet (OR 6.2; 95% CI 5.1–7.5). In addition, the odds of helmet use were noted to be significantly different depending on province, day of the week, time of day and number of passengers on the motorcycle. This study highlights the extremely low rate of child passenger helmet use in Cambodia, and provides priorities for interventions and enforcement to ensure all children are protected from head injury.